Inflation Targeting and Economic Performance: The Case of Mexico - Carrasco, Carlos A.; Ferreiro, Jesús (Panoeconomicus, 2011)
In the paper we analyze the impact of Inflation Targeting (IT) in Mexico. The objective is to evaluate the impact of the implementation of inflation targeting and full-fledged inflation targeting (FFIT) on the level and the variability of the inflation and the output in the Mexican economy. We conclude that inflation rates had been reduced in Mexico before the introduction of IT and FFIT. In our opinion, the structural reforms, including the Banxico reforms, are the main determinants of the decrease in inflation and its variability. The main impact of IT would have been the lock-in of inflation expectations around a low rate of inflation.Key words: Inflation, Mexico, Inflation targeting.JEL: E31, E52, E58, N16.